Diagnosa Penyakit Tulang Belakang pada Manusia Menggunakan Metode Case Based Reasoning - Iwid Hidayah Putri (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2024)
. Bones The spine is made up of 33 bones called vertebrae, which are connected by intertebral discs and ligaments. Spinal diseases are disorders or medical conditions that affect the structure of the spine, intervertebral discs, spinal cord, and the surrounding soft tissues. Spinal disease is a condition of the bones that results in the position or bending of the spine, this disease can refer to all ages. In medicine there is a problem that is a disease that leads to the human spine, which is the support of upholding the body and controlling movement, it is due to the lack of concern for the health of the spine and the limited basic understanding of the community about spinal diseases that cause death and imperfection of human organs. Spinal diseases can be degerative, inflammatory, traumatic, or even hereditary.